2023
DOI: 10.3389/fped.2023.1099372
|View full text |Cite
|
Sign up to set email alerts
|

Avatrombopag for the treatment of thrombocytopenia in children's patients following allogeneic hematopoietic stem-cell transplantation: A pilot study

Abstract: Thrombocytopenia following allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a common and life-threatening complication. Thus, new prevention and treatment strategies for post-HSCT thrombocytopenia are urgently required. In recent studies, thrombopoietin receptor agonists (TPO-RA) for treating post-HSCT thrombocytopenia indicated efficiency and safety. The improved effect of post-HSCT thrombocytopenia in adults was found in the administration of avatrombopag which was a new TPO-RA. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…14 However, it is not approved in the paediatric population; therefore, the treatment of ITP with AVA has only been reported in case (series) reports in this patient population. 8,15 The results of the phase 2, 28-day, double-blind, randomised clinical trial of AVA (20 mg) in adult patients with ITP showed that 80% patients achieved a platelet count response ≥50 × 10 9 /L with a 20 × 10 9 /L increase above baseline on day 28. In a randomised phase 3 clinical trial, 63% of patients treated with AVA achieved at least one response (platelet count ≥50 000/μL) by day 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, it is not approved in the paediatric population; therefore, the treatment of ITP with AVA has only been reported in case (series) reports in this patient population. 8,15 The results of the phase 2, 28-day, double-blind, randomised clinical trial of AVA (20 mg) in adult patients with ITP showed that 80% patients achieved a platelet count response ≥50 × 10 9 /L with a 20 × 10 9 /L increase above baseline on day 28. In a randomised phase 3 clinical trial, 63% of patients treated with AVA achieved at least one response (platelet count ≥50 000/μL) by day 8.…”
Section: Discussionmentioning
confidence: 99%
“…It has been approved by the FDA and EMA for the treatment of primary chronic ITP in adult patients and has demonstrated efficacy and safety in a previous study 14 . However, it is not approved in the paediatric population; therefore, the treatment of ITP with AVA has only been reported in case (series) reports in this patient population 8,15 …”
Section: Discussionmentioning
confidence: 99%
“…Another real-world study revealed the efficacy of eltrombopag in providing a rapid, sustained response that improves haematopoietic function in PGF patients [ 44 ]. Avatrombopag [ 45 , 46 ], hetrombopag [ 47 ], and romiplostim [ 48 ] have all been reported to improve platelet engraftment post-HSCT. A recent systematic review and meta-analysis has concluded that eltrombopag could provide an effective treatment option for PGF with an acceptable toxicity profile [ 49 ].…”
Section: Discussionmentioning
confidence: 99%